Whole genome characterization of reassortant G10P[11] strain (N155) from a neonate with symptomatic rotavirus infection: Identification of genes of human and animal rotavirus origin - Ramani, Sasirekha (Elsevier Science, 2009)
BACKGROUND: Rotavirus G10P[11] strains have long been associated with asymptomatic neonatal infections in some parts of India. We have previously reported G10P[11] strains associated with both asymptomatic infections and severe gastrointestinal disease in neonates from Vellore in southern India, with >90% partial nucleotide and amino acid identity to the VP4, VP6, VP7 and NSP4 genes of the exclusively asymptomatic G10P[11] strain I321. OBJECTIVES: In this study, the whole genome of a G10P[11] isolate (N155) from a neonate with severe gastrointestinal disease was characterized to determine whether there were significant differences in its genetic makeup in comparison to G10P[11] strain I321 and to establish the origin of the G10P[11] strains in Vellore. STUDY DESIGN: PCR amplification and complete genome sequencing was carried out for all 11 gene segments of symptomatic G10P[11] rotavirus isolate N155. Nucleotide and amino acid sequence similarity with I321, other human and bovine strains for each gene segment were determined. The origin of each gene was determined based on the degree of identity to bovine or human rotavirus strains. RESULTS: N155 was found to be a reassortant between human and bovine rotaviruses. With the exception of NSP2, gene sequences of strain N155 showed >90% identity to published sequences of I321. Gene segments encoding NSP1, 2 and 3 were of human rotavirus origin for both strains; however, phylogenetic analysis of NSP2 sequences indicated that the human parental strain that led to the origin of these bovine-human reassortant strains was different. There were no significant differences between NSP2 sequences of strains from symptomatic and asymptomatic neonates in the same setting. CONCLUSIONS: The study shows that the difference in clinical presentations in neonates may not be due to the limited variability in the genome sequence of G10P[11] strains and that G10P[11] strains in different parts of India could have evolved through reassortment of different parental strains.